INVESTIGATION OF RDE THERMAL PARAMETERS CHANGES IN RESPONSE TO LONG-TERM STATION BLACK OUT - Hendro Tjahjono (JURNAL TEKNOLOGI REAKTOR NUKLIR TRI DASA MEGA, 2017)
Due to long-term station black out (SBO) of the RDE (Experimental Power Reactor), the residual heat from the core will be removed to a residual heat removal system (RHRS). The objective of this study is to know the transient characteristic of RDE thermal parameters in response to the loss of residual heat removing ability for long-term. To achieve this objective, an analysis model of reactor thermal parameters changes during SBO, using Matlab program to simulate heat transfer equations of conduction, convection and radiation has been performed. Using this program, the changes of RDE thermal parameters until 800 hours after reactor trip have been analyzed. It is concluded that, in long-term SBO condition, the reactor is still safe with the maximum core temperature of 1140°C, which is still far under the safety limit of 1600°C as stated in the design criteria. More attentions are needed to be taken with the increasing of concrete temperature up to 600°C when the water storage is empty. Therefore, the availability of water in the RHRS shall absolutely be maintained.Keywords: experimental power reactor, residual heat removal, transient, Matlab. INVESTIGASI PERUBAHAN PARAMETER TERMAL RDE PADA KONDISI KEHILANGAN CATU DAYA LISTRIK DALAM JANGKA PANJANG. Akibat kehilangan catu daya listrik luar pada Reaktor Daya Eksperimental (RDE), panas sisa dari reaktor dibuang ke suatu sistem pembuang panas sisa. Penelitian ini bertujuan untuk mengetahui karakteristik transien parameter termal RDE ketika terjadi kegagalan pembuangan kalor sisa tersebut dalam jangka panjang. Untuk mencapai tujuan tersebut telah disusun model analisis perubahan parameter termal reaktor ketika terjadi Station Black Out (SBO) menggunakan pemrograman Matlab dengan melibatkan persamaan-persamaan perpindahan kalor secara konduksi, konveksi dan radiasi. Dengan menggunakan program ini perubahan parameter termal RDE hingga 800 jam setelah reaktor trip telah dianalisis. Disimpulkan bahwa pada kondisi SBO dalam jangka panjang tersebut, reaktor masih tetap aman dengan temperatur maksimum teras sebesar 1140 °C, yaitu masih jauh di bawah batas aman 1600 °C yang telah ditetapkan dalam kriteria desain. Perlu diperhatikan adanya peningkatan temperatur beton hingga 600 °C jika air pendingin sudah habis. Oleh karena itu, ketersediaan air pendingin di sistem pembuang panas sisa mutlak harus dijaga.Kata kunci: reaktor daya eksperimental, pembuang panas sisa, transien, Matlab.